2012
DOI: 10.1037/a0028252
|View full text |Cite
|
Sign up to set email alerts
|

The role of adult hippocampal neurogenesis in reducing interference.

Abstract: Adult neurogenesis in the hippocampal dentate gyrus plays an important role in learning and memory. However, the precise contribution of the new neurons to hippocampal function remains controversial. Emerging evidence suggests that neurogenesis is important for pattern separation and for mitigating interference when similar items must be learned at different times. In the present study, we directly test this prediction using a recently developed olfactory memory task that has those specific features. In this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…Irradiated rats also made more errors in a cued water maze when a high-interference task (using similar cues), but not an uncued low-interference task, was performed for several days between training and memory testing (Winocur et al 2012). The role of interference in impairment associated with loss of neurogenesis is also seen in a nonspatial interference task, in which rats without neurogenesis learn a list of odor pairs normally but then make more errors when learning a second list that repeats some of the same odors (Luu et al 2012). Taken together, these studies suggest that new neurons are more likely to play a role in behavioral tasks involving greater interference, yet even tasks with apparently high levels of potential interference can often be performed without adult neurogenesis.…”
Section: Function Of New Neurons In the Hippocampusmentioning
confidence: 99%
“…Irradiated rats also made more errors in a cued water maze when a high-interference task (using similar cues), but not an uncued low-interference task, was performed for several days between training and memory testing (Winocur et al 2012). The role of interference in impairment associated with loss of neurogenesis is also seen in a nonspatial interference task, in which rats without neurogenesis learn a list of odor pairs normally but then make more errors when learning a second list that repeats some of the same odors (Luu et al 2012). Taken together, these studies suggest that new neurons are more likely to play a role in behavioral tasks involving greater interference, yet even tasks with apparently high levels of potential interference can often be performed without adult neurogenesis.…”
Section: Function Of New Neurons In the Hippocampusmentioning
confidence: 99%
“…Interference is a prominent characteristic of many hippocampal dependent tasks that require subjects to respond appropriately to a cue that has been rewarded some times and not others (Agster et al, 2002; Fortin et al, 2002; Rajji et al, 2006; Smith et al, 2004) or that require memory for the events of the current trial without interference from previous trials (Olton and Papas, 1979). Disruption of adult hippocampal neurogenesis has also been shown to increase susceptibility to interference (Luu et al, 2012; Winocur et al, 2012). Pattern separation is another hippocampal mechanism for preventing interference by generating highly distinctive representations even when sensory input is similar (Colgin et al, 2008; Hunsaker and Kesner, 2013; Yassa and Stark, 2011).…”
Section: The Adaptive Value Of Hippocampal Context Representationsmentioning
confidence: 99%
“…In fact, memory interference may be a result of inadequate PS during memory acquisition or inadequate pattern completion during memory retrieval. Studies of memory interference under conditions of reduced adult neurogenesis show that, indeed, there is a relationship between the two (Wojtowicz et al 2008;Luu et al 2012;Winocur et al 2012). In all cases tested so far, memory interference became more pronounced when adult neurogenesis was reduced.…”
Section: Dn Abrous and Jm Wojtowiczmentioning
confidence: 99%
“…These studies also suggest that adult neurogenesis is relevant to separation of important stimuli from irrelevant, distracting stimuli. A good example of such studies is work by Luu et al (2012), which showed a recently developed hippocampal memory task depending on olfactory recognition of pairs of odors (Fig. 4).…”
Section: Dn Abrous and Jm Wojtowiczmentioning
confidence: 99%